2006
DOI: 10.1111/j.1528-1167.2006.00550.x
|View full text |Cite
|
Sign up to set email alerts
|

EEG Source Imaging in Pediatric Epilepsy Surgery: A New Perspective in Presurgical Workup

Abstract: Summary:Purpose: Epilepsy is a relatively frequent disease in children, with considerable impact on cognitive and social life. Successful epilepsy surgery depends on unambiguous focus identification and requires a comprehensive presurgical workup, including several neuroimaging techniques [magnetic resonance imaging, positron emission tomography (PET), and single-photon emission computed tomography (SPECT)]. These may be difficult to apply in younger or developmentally delayed children or both, requiring sedat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
99
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(107 citation statements)
references
References 65 publications
6
99
0
2
Order By: Relevance
“…On the other hand, theoretical studies have analytically shown that LORETA solution gives satisfactory results compared with other nonparametric inverse solution methods (Greenblatt et al, 2005;Grech et al, 2008). Direct comparisons of LORETA source estimation with intracranial recordings and electrocortical stimulation (Fuchs et al, 1999;Lantz et al, 1996;Michel et al, 1999;Zumsteg et al, 2006), fMRI (Groening et al, 2009;Schulz et al, 2008;Vulliemoz et al, 2009), and with postsurgical outcome (Michel et al, 2004;Sperli et al, 2006;Michel et al, 2012) show that LORETA can reliably identify intracranial sources. Therefore, functional connectivity patterns can be estimated by different source reconstruction approaches by which similar results will be approached.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, theoretical studies have analytically shown that LORETA solution gives satisfactory results compared with other nonparametric inverse solution methods (Greenblatt et al, 2005;Grech et al, 2008). Direct comparisons of LORETA source estimation with intracranial recordings and electrocortical stimulation (Fuchs et al, 1999;Lantz et al, 1996;Michel et al, 1999;Zumsteg et al, 2006), fMRI (Groening et al, 2009;Schulz et al, 2008;Vulliemoz et al, 2009), and with postsurgical outcome (Michel et al, 2004;Sperli et al, 2006;Michel et al, 2012) show that LORETA can reliably identify intracranial sources. Therefore, functional connectivity patterns can be estimated by different source reconstruction approaches by which similar results will be approached.…”
Section: Discussionmentioning
confidence: 99%
“…The simplified realistic head model offers an easy and fast extraction of the head model and a fast and accurate analytical solution to the forward problem at the expense of being maybe somewhat less precise than finite element models based on the individual anatomy. Nevertheless, accurate source localization using this head model has been demonstrated in different clinical and experimental studies in the past [Groening et al, 2009;Michel et al, 2004;Phillips et al, 2005;Sperli et al, 2006;Vulliemoz et al, 2009].…”
Section: Analysis Of Pre-stimulus Source Differencesmentioning
confidence: 99%
“…Although several analytical software techniques can be used to establish indirect indices of source localization to improve the spatial resolution of d EEG, the HydroCel Geodesic Sensor Net (HCGSN) by Electrical Geodesics, Inc. (EGI), a dense sensory array that maintains equal distances among adjacent recording electrodes on all surfaces of the scalp, further enhances spatial resolution 4,5,6 compared to standard d EEG systems. The sponge-based HCGSN can be applied rapidly and without scalp abrasion, making it ideal for use with adults 7,8 , children 9,10,11 , and infants 12 , in both research and clinical 4,5,6,13,14,15 settings. This feature allows for considerable cost and time savings by decreasing the average net application time compared to other d EEG systems.…”
mentioning
confidence: 99%
“…Here we present an overview of an established methodology that represents a significant improvement on conventional methodologies for studying EEG in infants and adults. Although several analytical software techniques can be used to establish indirect indices of source localization to improve the spatial resolution of d EEG, the HydroCel Geodesic Sensor Net (HCGSN) by Electrical Geodesics, Inc. (EGI), a dense sensory array that maintains equal distances among adjacent recording electrodes on all surfaces of the scalp, further enhances spatial resolution 4,5,6 compared to standard d EEG systems. The sponge-based HCGSN can be applied rapidly and without scalp abrasion, making it ideal for use with adults 7,8 , children 9,10,11 , and infants…”
mentioning
confidence: 99%
See 1 more Smart Citation